A STUDY ON CONVERSION OF RAW COW MANURE INTO NUTRITIOUS ORGANIC FERTILIZER FOR QUALITY ENHANCEMENT - Padwal, Rahul Prataprao; Kulkarni, Milind Audumbar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Due to increasing awareness of sustainable agriculture practices, has generated the necessity of proper composting processing methods to enhance the quality of raw cow manure as an organic fertilizer. The current study examines the effect of different microbial inoculants on the composting process emphasising on balancing the C:N ratio, enhancing the nutrients, reducing heavy metals and eliminating entire pathogens. Experiment was carried out based on four different composting treatments: T1 (Control, without inoculants), T2 (Bacterial Inoculant – Bacillus, Pseudomonas), T3 (Fungal Inoculant – Trichoderma, Aspergillus), and T4 (Mixed- Bacterial & Fungal Inoculants.). Compost windrows were monitored about 60-days duration for vital parameters, such as C:N ratio reduction, retention of organic Nitrogen, solubilization of Phosphorus, control of pathogens, and the degradation of heavy metals. The result shows that T4- (Bacteria + Fungi in Combination) has enhanced in compost quality and maturity the most. The significant decrease in C: N ratio of the compost from 30:1 to 14:1, indicates the proper decomposition of the organic matter. Regarding nutrient content T4 has found higher level of Nitrogen as N (1.42%), Phosphorus as P2O5 (1.10%) and Potassium as K2O (1.85%) compared to other treatments T1, T2, T3, indicates the better nutrient retention (Awasthi et al., 2022). The pathogen such as E. coli and Salmonella completely disappeared in T4 followed by pathogen test of the compost, due to the prolonged thermophilic conditions (55–70°C) developed during the composting process in the windrow (Reddy et al., 2018). The significant drop is observed heavy metals such as Chromium (Cr: 15.3 to 5.9 ppm), Cadmium (Cd: 2.4 to 0.6 ppm), Lead (Pb: 12.5 to 4.8 ppm) in the T4 after heavy metals analysis which shows the compost safe for long-term soil application (Dai et al., 2020). These findings clearly indicates that using compost derived from T4 microbial consortia may be the effective strategy for enhancing the quality of organic manure, It also makes the organic manure nutritious and balanced, pathogen-free, and eco-friendly organic fertilizer. Economic viability and widespread adoption of this process in sustainable agricultural practices must be our top priorities in our future work.